WITHOUT COMPLICATIONS: DO THESIS, DO RESEARCH - Hernández Hernández, Oscar Misael (Libros UAT, 2018)
In these books, the importance and academic benefits of doing a bachelor's thesis are seldom rescued, and rarely do we find publications that express in an entertaining and colloquial way the benefits of doing research. In that sense, Without complications: doing thesis, doing research, it does not pretend to be a tedious recipe for the practice of research, where only scholars and "cults" have the license to do so; this publication rather aims to motivate the student in general to the adventure of thesis.